PENGARUH EKSTRAK JAHE MERAH (Zingiber officinale) DAN MADU TERHADAP KADAR KOLESTEROL TOTAL TIKUS MODEL DIABETES MELITUS - Alfi Muntafiah; Dita Yulianti; Aulia Husna Cahyaningtyas; Hani Ismi Damayanti (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
Diabetes mellitus (DM) is a disease characterized by elevated blood glucose levels (hyperglycemia) caused by deficiency of insulin, and insulin resistance or both. This chronic disease prevalence is increasing nationally and globally. This study aimed to determine the effect of ginger extract and honey various doses on levels of total cholesterol in the Wistar diabetic rat model induced by alloxan. This research is true experimental post-test only with control group design. Subject of the study 30 male Wistar rats weight 150-200 grams, divided into 6 groups: A) healthy controls (K1), B) DM control (K2), C) Treatment with red ginger extract 1000 mg / kg and honey 1 ml / kg (K3), D) Treatment with ginger extract red 1000 mg / kg and honey 2 ml / kg (K4), E) Treatment with red ginger extract 500 mg / kg and honey 1 ml / kg (K5), F) Treatment with red ginger extract 500 mg / kg and honey 2 ml / kg (K6). DM induction by alloxan 160 mg / kg intraperitoneally for 5 days, and the provision of treatment for 14 days. Total cholesterol levels were measured by CHOD-PAP method. Results: The mean total cholesterol levels of healthy control group vs the diabetic control 58.20 ± 8.76 vs. 87.80 ± 5.81 mg / dL. Based on one way ANOVA test, red ginger extract and honey various doses significantly lower total cholesterol level (p <0.05). The mean total cholesterol levels between the group K3 to K4 was not statistically different, as well as K5 with K6. However, mean total cholesterol levels at K3 and K4 differ significantly from the K5 and K6. Conclusion: Combination of red ginger extract and honey can lower total cholesterol levels in diabetic rat model induced by alloxan.